Exploring university students' perceptions of generative artificial intelligence in education - Mădălina Lavinia Țală; Cătălina Nicoleta Müller; Irina Albăstroiu Năstase; Olimpia State; Georgică Gheorghe (Amfiteatru Economic, 2024)
Artificial intelligence, the latest chapter of the technological revolution, has a tremendous potential to change every area of our lives. This article has focused on a specific form of artificial intelligence, namely generative intelligence, which facilitates the generation of content in all its forms (text, image, video, audio, programming codes, etc.). Thus, generative artificial intelligence has a crucial role in education, allowing for the personalisation of educational content and facilitating the learning process. In the beginning, the paper has highlighted conceptual delimitations regarding artificial intelligence and its applications in education, along with advantages and limitations, highlighting that the adoption of generative artificial intelligence solutions, such as ChatGPT, in higher education in economics has been relatively underexplored in the literature. In order to cover these gaps identified in the literature, have been presented, in the second part of the paper, the methodology and results of an exploratory research, conducted on a sample of 364 undergraduate and master's students at the Faculty of Business and Tourism within the Bucharest University of Economic Studies. The research has provided insight into the perception of Business Administration students regarding these applications. The results indicated a high level of awareness and interest in content generation models and highlighted that users with favourable perceptions regarding the quality of content generated by such applications tend to believe that their integration into academic endeavours can foster creativity and enhance employment prospects.
Keywords: M19; O33; 330; generative artificial intelligence; ChatGPT; perceptions; competencies; higher education in economics